2002
DOI: 10.1093/brain/awf240
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolite changes in cortical grey and normal-appearing white matter in clinically early relapsing-remitting multiple sclerosis

Abstract: While much work has concentrated on focal white matter (WM) lesions in multiple sclerosis, there is growing evidence to suggest that normal-appearing WM (NAWM) and grey matter (GM) are also involved in the disease process. This study investigated multiple sclerosis disease effects on NAWM and cortical GM (CGM) metabolite concentrations, and the relationships between these metabolite concentrations and clinical impairment. Proton magnetic resonance spectroscopic imaging ((1)H-MRSI) data acquired using point res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
198
7
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(232 citation statements)
references
References 64 publications
24
198
7
3
Order By: Relevance
“…Decreased NAA has also been observed in cortical gray matter in early relapsing remitting MS, suggesting that early neuronal cell body damage is occurring. 38 It is reduced by ϳ20% in thalamic gray matter in secondary progressive MS and in a postmortem study the decrease in NAA (accompanied by atrophy) was associated with decreased numbers of neurones. 7 In primary progressive MS, reduction of NAA and atrophy appear to be relatively independent of T2 lesion load.…”
Section: Mr Spectroscopy: N-acetyl Aspartatementioning
confidence: 89%
See 1 more Smart Citation
“…Decreased NAA has also been observed in cortical gray matter in early relapsing remitting MS, suggesting that early neuronal cell body damage is occurring. 38 It is reduced by ϳ20% in thalamic gray matter in secondary progressive MS and in a postmortem study the decrease in NAA (accompanied by atrophy) was associated with decreased numbers of neurones. 7 In primary progressive MS, reduction of NAA and atrophy appear to be relatively independent of T2 lesion load.…”
Section: Mr Spectroscopy: N-acetyl Aspartatementioning
confidence: 89%
“…37 It is also observed in NAWM, in which the elevation has been correlated with disability in MS patients with both short and long disease durations. 38,39 Ins is produced by glial cells and is a potential marker of astrocytosis, gliosis, or possibly microglial activation. Although Ins is difficult to quantify because of having a short T2 relaxation time (thus requiring MR spectroscopy with a short echo time), these interesting observations-suggesting it may detect a diffuse glial/inflammatory process associated with disease progression-should encourage further investigation of Ins in therapeutic trials.…”
Section: Mrimentioning
confidence: 99%
“…These abnormal conditions have been demonstrated both in lesions and in normal-appearing white matter (NAWM) and normal-appearing gray matter (NAGM). [1][2][3][4][5][6][7][8][9][10] T1-and T2-weighted MR imaging is currently the diagnostic reference to define and monitor MS, but it has poor specificity and sensitivity in detecting pathophysiologic MS changes correlated with clinical disability. 6,[11][12][13][14][15] For some years, brain proton MR spectroscopy ( 1 H-MR spectroscopy) has been used to study MS by offering a unique opportunity to evaluate biochemical changes that could shed light on the complex pathophysiology of the disease and potentially define new markers correlated with the clinical evolution of MS. 1,16 Many cerebral quantitative MR spectroscopy studies in patients with MS have evaluated the correlation of the specific single metabolites with specific physiologic events during the MS disease course.…”
Section: Ultiple Sclerosis (Ms) Is a Central Nervous System (Cns)mentioning
confidence: 99%
“…11,[15][16][17][18][19][20] Besides the axonal damage within the NAWM, the glial cell activity is increasingly becoming an area of interest in patients with chronic inflammatory diseases of the central nervous system (CNS). Several studies have already demonstrated a significant increase of mIns in the NAWM of patients with definite MS. [20][21][22][23] Metabolic alterations in the NAWM of patients with CIS are also of particular interest because these changes might have prognostic relevance for the clinical outcome and might be helpful to exclude other differential diagnoses. The results of recently performed 1 H-MR spectroscopy studies focusing on this topic are inconclusive so far.…”
mentioning
confidence: 99%